DESIGNING WITH VERANDA IN JAVANESE ARCHITECTURE - Mohamad Muqoffa (Journal of Architecture&ENVIRONMENT, 2013)
The traditional architecture in Indonesia has been implementing local wisdom or genius loci to sustain both their tradition and built environment. In contrast, the modernity and global paradigm reduce the local paradigm. In fact, most tradition-al/vernacular built environment has many potential aspects, such as design of roof, building material etc. Omah Laweyanan has implemented some elements of building which refer to ecological architecture. Those are design of roof, doors and windows, and yard of house [open space] and veranda. The doors and windows have shape and size which cross ventilation be done. This paper consist of discussion that ve-randa are an approach and design strategy in Javanese Architecture, which they can sustain the environment. This paper will focus on omah Laweyanan in Surakar-ta. According to field study, it shows that veranda in omah Laweyanan is an alter-native that attempts to minimize the impact of global warming and climate change, which can be developed through the implementation in architecture design.